2018
DOI: 10.3748/wjg.v24.i6.752
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of hepatitis B-antibody loss and a case report ofde novohepatitis B virus infection in a child after living-donor liver transplantation

Abstract: AIMTo assess the seroprevalence of hepatitis B virus (HBV) immunity among previously vaccinated pediatric liver transplant recipients and present a case report of de novo hepatitis B infection after liver transplantation.METHODSThis study focused on children with chronic liver diseases who received primary hepatitis B immunization and had a complete dataset of anti-HBs before and after liver transplantation between May 2001 and June 2017. Medical records were retrospectively reviewed for potential factors rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
10
2
Order By: Relevance
“…This is particularly worrying, as Leung et al found insufficient antibody titers in in 67% of fully vaccinated children with Hepatitis B after liver transplantation [16]. Moreover, despite complete HBV vaccination, infection may occur post-transplant as case reports suggest [17].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly worrying, as Leung et al found insufficient antibody titers in in 67% of fully vaccinated children with Hepatitis B after liver transplantation [16]. Moreover, despite complete HBV vaccination, infection may occur post-transplant as case reports suggest [17].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, serology testing and immunization may be valuable in these groups. There is a reported case in which de novo hepatitis B infection was diagnosed 3 years after a liver transplant despite the recipient having undergone complete hepatitis B immunization pre-transplant[ 26 ]. This demonstrates that complete hepatitis B immunization pre-liver transplant does not guarantee post-transplant protection.…”
Section: Discussionmentioning
confidence: 99%
“…That case prompted us to instigate a protocol for reimmunization and hepatitis B surface antibody monitoring every 3-6 mo to maintain a protective level of > 100 mIU/mL. De novo hepatitis B in the aforementioned boy who had hepatitis B surface antibody > 1000 mIU/mL pretransplant[ 26 ] may reflect waning immunity post-liver transplant. As well as vaccination, research evaluating the humoral and cellular immunity evoked by each vaccine should be conducted to determine vaccination schedules and the antibody parameters required to prevent VPIs more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, a booster dose is not indicated if they had been primarily immunised, because the rapid anamnestic response could occur after HepB exposure [4]. Unlike healthy persons, disappearance of HB antibodies in liver-transplanted children might indicate loss of protection, as evidenced by de novo HepB infection (DNH) [5]. There has been no cut-off anti-HB level that is adequate for DNH prevention.…”
Section: Introductionmentioning
confidence: 99%